2022
DOI: 10.1186/s40813-022-00255-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the mcr-1 gene prevalence in Spanish food-producing pigs from 1998 to 2021 and its relationship with the use of polymyxins

Abstract: Background Resistance to colistin was an uncommon phenomenon traditionally linked to chromosome point mutations, but since the first description of a plasmid-mediated colistin-resistance in late 2015, transmissible resistance to colistin has become a Public Health concern. Despite colistin is considered as a human last resort antibiotic, it has been commonly used in swine industry to treat post-weaning diarrhoea in piglets. However, the progressively increase of colistin resistance during the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…We suggest the monitoring of pathogenic (invasive) E. coli in surveillance programs to accurately determine the persistence of colistin resistance. Our findings on the decrease in colistin-resistant mcr-bearing isolates would reinforce the conclusions of longitudinal studies on the mcr-1 abundance in food-producing pigs, and its relationship with the use of polymyxins (Wang et al, 2020;Miguela-Villoldo et al, 2022). Thus, Miguela-Villoldo et al (2022) reported the decreasing trend of colistin resistance associated with mcr-1 gene in Spain, since the EMA and AEMPS strategies were applied in 2016 to reduce colistin use in animals.…”
Section: Phylogeny Mcr and Esbl Genes: Monitoring Toolsupporting
confidence: 83%
See 1 more Smart Citation
“…We suggest the monitoring of pathogenic (invasive) E. coli in surveillance programs to accurately determine the persistence of colistin resistance. Our findings on the decrease in colistin-resistant mcr-bearing isolates would reinforce the conclusions of longitudinal studies on the mcr-1 abundance in food-producing pigs, and its relationship with the use of polymyxins (Wang et al, 2020;Miguela-Villoldo et al, 2022). Thus, Miguela-Villoldo et al (2022) reported the decreasing trend of colistin resistance associated with mcr-1 gene in Spain, since the EMA and AEMPS strategies were applied in 2016 to reduce colistin use in animals.…”
Section: Phylogeny Mcr and Esbl Genes: Monitoring Toolsupporting
confidence: 83%
“…Our findings on the decrease in colistin-resistant mcr-bearing isolates would reinforce the conclusions of longitudinal studies on the mcr-1 abundance in food-producing pigs, and its relationship with the use of polymyxins (Wang et al, 2020;Miguela-Villoldo et al, 2022). Thus, Miguela-Villoldo et al (2022) reported the decreasing trend of colistin resistance associated with mcr-1 gene in Spain, since the EMA and AEMPS strategies were applied in 2016 to reduce colistin use in animals. Likewise, Wang et al, 2020 showed a substantial reduction in sales of colistin in animals (2015)(2016)(2017)(2018), after the withdrawal of colistin as growth promoter in China in 2017, which was rapidly followed by a significant reduction in the prevalence of mcr-1 in both the animal and human sectors.…”
Section: Phylogeny Mcr and Esbl Genes: Monitoring Toolsupporting
confidence: 83%
“…Similar results were reported from Spain. Miguela-Villoldo et al described a steady increase of mcr-1 in bacteria from cecal samples from pigs between 2004 and 2015 and a downward trend between 2017 and 10.3389/fmicb.2022.1076315 (Miguela-Villoldo et al, 2022. Another group from Spain screened 200 E. coli isolates collected in 1999 to 2018 from swine and reported a peak of colistin resistance (17.5% of the strains) in 2011-2014 (Aguirre et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to colistin has been usually low in Spain, even when this drug was used massively in the pig sector [44,47]. The application of the Spanish Plan against Antibiotic Resistance in 2015, and the subsequent reduction in colistin consumption by more than 95% [48], may have contributed to an overall reduction in the detection of the mcr-1 gene [49,50], explaining the absence of phenotypic resistance against colistin in these isolates. Regarding AMR to third-generation cephalosporins, this was found in 5% of the Salmonella isolates.…”
Section: Discussionmentioning
confidence: 99%